(untitled) - Byerly, Greg (New York, 1980)
This book is a selective, annotated bibliography on pornography, encompassing, psychological, sociological, religious, philosophical, legal and popular persectives.
Keywords: Pornography,Pornography,Sự khiêu dâm,Sự khiêu dâm; Social aspects,Bibliography,Psychological aspects,Bibliography,Khía cạnh xã hội,Khía cạnh tâm lý; United States,United States,Hoa Kỳ,Hoa Kỳ